Learning How to Be Infinite - Pablo Montosa (Public Reason)
This paper focuses on some of the more controversial points in Jenny Bunker’s reply to Adrian W. Moore concerning his account of Spinoza. In particular, it raises the question of whether Moore has conceived of certain aspects of the relations between modes in a substantial manner and points to some of the consequences that would follow. Finally, it argues, contra Moore, that the perspective sub specie aeternitatis does not imply draining reality of all value and meaning but conceiving of values as relative. In contrast, the perspective in mediis rebus implies conceiving of values as substantial attributes of things, being the cause that ultimately leads to nihilism, understood as contempt for the world.